Solubilização de elementos e substâncias químicas de cerâmica vermelha agregada com resíduos de beneficiamento de rochas ornamentais - Freitas, Alcione Alves de (2022)
Brazil is one of the largest producers of ornamental stones and the state of Espírito Santo stands out as the largest exporter in the country, accounting for 81% of exports. In the midst of this great promising conjuncture, the ornamental stone sector generates large amounts of waste in the stone processing process, including fine waste that has a diverse mineralogical and chemical constitution and, when improperly discarded, can cause impacts. environment, contaminating water and soil. Therefore, having verified the capacity of the ceramic sector to absorb these residues and use them in its production process, as well as the stabilization and encapsulation of the chemical elements in the glassy phase formed, the objective of this work was to characterize the residues produced in the processing of ornamental stones by through solubilization, granulometry, XRD and XRD tests and apply them in the production of red ceramics. The specimens were made with 80% clay, 20% residue and 10% (m/m) moisture, they were sintered at 1000°C. The concentration of Al, Fe, Mn and Pb in the residues and the concentration of Al and Mn in the clays was above the stipulated by NBR 10004. The sintering, grinding and grinding of ceramics had a great effect on the concentration of elements, and grinding caused a greater release of these elements. As a result, the use of dimension stone waste for the production of red ceramics is shown to be an appropriate route for its disposal, as its use does not negatively affect the final concentration of elements in the solubilized extract.